The Effect of Green Supply Chain Management on Customer Effectiveness in the Presence of Environment Orientation and Supply Chain Orientation - Saudi, Mohd Haizam Mohd; Ridwansyah, Iwan; Saefudin, Nugraha; Mohd, Rd. Herman Sofiandi; Razimi, Shahril Bin Ahmad (ExcelingTech, 2019)
The purpose of the study is to define the effect of environment orientation on GSCM, to discuss the supply chain orientation on GSCM, to determine the effect of GSCM on customer effectiveness and the mediating role of GSCM between environment orientation, SCO and customer effectiveness. This is a quantitatively study and 5point Likert scale is used to collect the data. Random sampling technique is used on the 200 respondents from Indonesia manufacturing firms. PLS3 is used to analyze the data. This study concludes that customer effectiveness can be enhanced though the perception of taking environmental friendly steps from the organization. HR plays the pivotal role in this regard in forming the strategy to boost the GSCM.